2019
DOI: 10.3847/2041-8213/ab2a14
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Close-separation Binary Quasar at the Heart of a z ∼ 0.2 Merging Galaxy and Its Implications for Low-frequency Gravitational Waves

Abstract: Supermassive black hole (SMBH) binaries with masses of ∼ 10 8 -10 9 M are expected to dominate the contribution to the as-yet undetected gravitational wave background (GWB) signal at the nanohertz frequencies accessible to Pulsar Timing Arrays (PTA). We currently lack firm empirical constraints on the amplitude of the GWB due to the dearth of confirmed SMBH binaries in the required mass range. Using HST/WFC3 images, we have discovered a z ∼ 0.2 quasar hosted in a merger remnant with two closely separated (0.13… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…The absolute number of TOAs, as well as the number of timing model parameters (including parameterizations of the noise), play a determining role in the time it takes to perform GW analyses of PTA data (van Haasteren & Vallisneri 2015, 2014Ellis et al 2013;Lentati et al 2013b). Advanced data analysis techniques to handle this deluge of TOAs will need to be significantly improved if we want to avoid delays on the numerous science deliverables offered by PTAs (Cordes et al 2019;Fonseca et al 2019;Goulding et al 2019;Kelley et al 2019;Lynch et al 2019;Mingarelli 2019;Siemens et al 2019;Stinebring et al 2019;Taylor et al 2019).…”
Section: ∼0mentioning
confidence: 99%
“…The absolute number of TOAs, as well as the number of timing model parameters (including parameterizations of the noise), play a determining role in the time it takes to perform GW analyses of PTA data (van Haasteren & Vallisneri 2015, 2014Ellis et al 2013;Lentati et al 2013b). Advanced data analysis techniques to handle this deluge of TOAs will need to be significantly improved if we want to avoid delays on the numerous science deliverables offered by PTAs (Cordes et al 2019;Fonseca et al 2019;Goulding et al 2019;Kelley et al 2019;Lynch et al 2019;Mingarelli 2019;Siemens et al 2019;Stinebring et al 2019;Taylor et al 2019).…”
Section: ∼0mentioning
confidence: 99%
“…Massive black hole (BH) binaries, emitting nano-Hz GWs, are the most prominent IPTA sources (Burke-Spolaor et al 2019). Therefore, observational evidence for the existence of such binaries has important IPTA implications (Goulding et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Begelman et al 1980) has not been observed yet. But earlier steps have been explored, and several dual AGNs, which is a late stage of a galaxy merger (Genzel et al 2001;Koss et al 2016Koss et al , 2018Goulding et al 2019), or even a triple nucleus (Deane et al 2014;Pfeifle et al 2019), have been detected. While about 40% of ultra-luminous infrared galaxies exhibit a double nucleus (Cui et al 2001), Koss et al (2018) discuss that gas-rich luminous AGNs are often hidden mergers.…”
Section: Introductionmentioning
confidence: 99%